Otimização de formulação de revestimento comestível para conservação pós-colheita de goiaba (Psidium guajava) - Carvalho, Luana Caliandra Freitas de (2019)
The edible coatings used are one of the most recent alternatives to aid in the preservation of food. They have excellent barrier properties, mainly to the transport of gases and water vapor, among other factors that contribute to the maintenance of post-colehite fruit quality. Guava (Psidium guajava) is widely consumed in natura, yet has a high respiratory rate, maturing rapidly, senescence during storage at room temperature. The present work aims to optimize and apply the best formulation of the edible coating containing sodium alginate and glycerol as variables, using a Rotational Central Compound Design (DCCR), considering post-harvest responses of guavas during storage. Based on this factorial design, surfaces with postharvest response curves and analysis of variance were performed to evaluate the effects and significance of the models of sodium and glycerol alginate generated by the Design-Expert® program (Stat-Ease-USA) . From these data using the Design-Expert® program (Stat-Ease-USA), it was possible to optimize the formulations of the edible coating, Doptimum, obtaining concentrations of 2.65% of sodium alginate and 0.36% of glycerol for the optimized coating. In the optimized formulation, shelf life analyzes were performed, allowing the evaluation of the coating behavior applied to the fruit on post-harvest responses after 25 days storage at room temperature and UR 80%. A significant difference was observed at 5% probability by the t-test between the control fruits (No coating application) and the treatment fruits (with optimized coating application) in the main post-harvest responses (PM, ATT, pH, SST , L*, a* and b*) evaluated from the fifth day of storage. To evaluate the coating, UV-VIS spectroscopy was performed, confirming the good formation and stability of the nanoparticles and silver and clove extract during the days: 1, 6 and 20 days of coating storage. Atomic absorption spectroscopy (FAAS) was used to determine silver in guava coated, with a positive result of presence of silver only in the fruit house, as expected. The results of the physical and physico-chemical analyzes for the optimized coating formulation were efficient in delaying maturation during the 25 days storage of the guavas at room temperature. The edible coating developed in this research proved to be appropriate, allowing the senescence challenge and consequent expansion of post-harvest life of guavas.